+0  
 
0
43
1
avatar

Suppose f ( x ) = − 9 x + 5 , while a = − 8 and b = 6. Compute the following:

 

A.) f ( a ) + f ( b ) =

 

B.) f ( a ) − f ( b ) =

 Sep 9, 2022
 #1
avatar+2 
+1

f(x)=-9x+5

 

Substitute for a   a=-8

f(a)=-9•(-8)+5

f(a)=77

 

Substitute for b   b=6

f(b)=-9•6+5

f(b)=-49

 

Substitute for f(a) and f(b)   f(a)=77   f(b)=-49

A.) 77+(-49) = 77-49 = 28

B.) 77-(-49) = 77+49 = 126

 

Hope this helps!!

 Sep 11, 2022
edited by Mathlover11  Sep 11, 2022
edited by Mathlover11  Sep 11, 2022

8 Online Users

avatar